PENGARUH PENERAPAN SIPANTES TERHADAP PENGEMBANGAN KARIR ASN DI BKPSDM KABUPATEN SUMEDANG - Supriatna, Ifal Nurfalah (JRPA - Journal of Regional Public Administration, 2025)
This study aims to analyze the impact of implementing the Integrated ASN Information System of Sumedang (SIPANTES) on the career development of State Civil Apparatus (ASN) at the Employee and Human Resource Development Agency (BKPSDM) of Sumedang Regency. This research uses a descriptive analysis method with a quantitative approach, and the type of statistics used is descriptive statistics. The sampling technique employed is nonprobability sampling, specifically saturated sampling, where all members of the population, totaling 43 ASN at BKPSDM Sumedang Regency, were included in the study. The implementation of SIPANTES is measured through five dimensions: system usage level, user satisfaction, positive attitude towards the system, achievement of system objectives, and financial payoff, with an overall percentage result of 89.58%, categorized as very good. The career development of ASN is measured through career clarity, self-development, and performance improvement, with a result of 84.5%, also categorized as very good. The correlation analysis results show a positive and significant relationship between the implementation of SIPANTES and ASN career development, with a correlation value of 0.628 (strong category). Furthermore, the regression analysis results indicate that the implementation of SIPANTES has a positive and significant effect on ASN career development with a determination coefficient of 39.5%, while the remaining 60.5% is influenced by other factors. Therefore, it can be concluded that the implementation of SIPANTES contributes to the improvement of ASN career development within the BKPSDM of Sumedang Regency.